Evaluating key characteristics of ideal colorectal cancer screening modalities: the microsimulation approach - Deibel, Rudolf Ansgar; Deng, Lu; Cheng, Chih-Yuan; Schlander, Michael; Ran, Tao; Lang, Brian; Krupka, Niklas; Beerenwinkel, Niko; Rogler, Gerhard; Wiest, Reiner; Sonnenberg, Amnon; Poleszczuk, Jan; et al. (Gastrointestinal endoscopy, 2021)
Background and Aims - Screening for colorectal cancer (CRC) can effectively reduce CRC incidence and mortality. Besides colonoscopy, tests for the detection of biomarkers in stool, blood, or serum, including the fecal immunochemical test (FIT), ColoGuard, Epi proColon, and PolypDx, have recently been advanced. We aimed to identify the characteristics of theoretic, highly efficient screening tests and calculated the effectiveness and cost effectiveness of available screening tests. - Methods - Using the microsimulation-based colon modeling open-source tool (CMOST), we simulated 142,501 theoretic screening tests with variable assumptions for adenoma and carcinoma sensitivity, specificity, test frequency, and adherence, and we identified highly efficient tests outperforming colonoscopy. For available screening tests, we simulated 10 replicates of a virtual population of 2 million individuals, using epidemiologic characteristics and costs assumptions of the United States. - Results - Highly efficient theoretic screening tests were characterized by high sensitivity for advanced adenoma and carcinoma and high patient adherence. All simulated available screening tests were effective at 100% adherence to screening and at expected real-world adherence rates. All tests were cost effective below the threshold of 100,000 U.S. dollars per life year gained. With perfect adherence, FIT was the most effective and cost-efficient intervention, whereas Epi proColon was the most effective at expected real-world adherence rates. In our sensitivity analysis, assumptions for patient adherence had the strongest impact on effectiveness of screening. - Conclusions - Our microsimulation study identified characteristics of highly efficient theoretic screening tests and confirmed the effectiveness and cost-effectiveness of colonoscopy and available urine-, blood-, and stool-based tests. Better patient adherence results in superior effectiveness for CRC prevention in the whole population.
Gesehen am 18.08.2021